Memorandum of understanding for strategic collaboration between Universiti Teknologi MARA and Gyeongsang National University / Fakulti Kejuruteraan Mekanikal - Universiti Teknologi MARA, Fakulti Kejuruteraan Mekanikal (Universiti Teknologi MARA (UiTM), 2020)
UiTM and Gyeongsang National University will endeavour to strengthen, promote and develop cooperation on the basis of equality and mutual benefit.